Consider the function
f ( x ) = x + x + x + ⋯ .
If the gradient of the tangent of the function at x = 1 2 can be expressed as b a , where a and b are coprime positive integers, what is the value of a + b ? .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f(x)=-3 can also be rejected by giving the argument that square root of a positive number will be a positive number.
same :)
Perfect. It's a really great answer. Thank you so much
Thanks Brother.. Great Answer
When you factorise, in the sixth passage, you assumed x=12. You should have written (f(12)-4)(f(12)-3)=0 because the equation is Not True for all x. Great Work anyway imho.
bt the question says the two no.s are coprime.. 1 and 7 are not coprime.infact 1 is not a prime no.
Log in to reply
coprime numbers are numbers who's common factors are only 1. Since the common factors of 1 and 7 is 1, therefore they're coprime. :)
The gradient of the tangent of the function f is ∇ f ( x ) = ∂ x ∂ f ( x ) = d x d f ( x ) = f ′ ( x ) , so let's work on the function by doing some algebra. First of all write it like this form, f ( x ) = x + f ( x ) , derivind using the chain rule f ′ ( x ) = 2 x + f ( x ) 1 + f ′ ( x ) , not a lot of algebra we can clear easily f'(x) and get this form f ′ ( x ) = 2 x + f ( x ) − 1 1 , and finally doing the substitution on x=12 f ′ ( 1 2 ) = 2 1 2 + f ( 1 2 ) − 1 1 , but we have another problem here; what is f(12) ? So by the definition f ( 1 2 ) = 1 2 + f ( 1 2 ) , squaring both sides f ( 1 2 ) 2 = 1 2 + f ( 1 2 ) f ( 1 2 ) 2 − f ( 1 2 ) − 1 2 = 0 ( f ( 1 2 ) − 4 ) ( f ( 1 2 ) + 3 ) = 0 , so taking the positive root we have f ( 1 2 ) = 4 , and subtituing on the derivate we finally get this f ′ ( 1 2 ) = 2 1 2 + f ( 1 2 ) − 1 1 f ′ ( 1 2 ) = 2 1 2 + 4 − 1 1 f ′ ( 1 2 ) = 2 1 6 − 1 1 f ′ ( 1 2 ) = 8 − 1 1 f ′ ( 1 2 ) = 7 1 , so f ′ ( 1 2 ) = 7 1 = b a , so a + b = 1 + 7 = 8
The question is somewhat confusing I think (Please correct me if I am wrong.)
Question simply wants us to calculate d x d f at x = 1 2 .
Now since there is infinite sequence of square roots for f ( x ) , we can write,
f ( x ) = x + f ( x )
∴ f ( x ) 2 = x + f ( x )
Differentiating both sides w.r.t.x, we get,
2 f ( x ) d x d f = 1 + d x d f
∴ d x d f = 2 f ( x ) − 1 1
∴ d x d f ∣ x = 1 2 = 2 f ( 1 2 ) − 1 1
Now we want to find out f ( 1 2 ) . Let f ( 1 2 ) = y .
∴ y 2 = 1 2 + y
This gives, y = 4 and y = − 3
But the answer which we get using y = − 3 violets the condition of positiveness asked in the problem hence y = 4 is the correct choice. This gives:
d x d f ∣ 1 2 = 7 1 and hence, a + b = 8
There is no confusion at all. The solution is completely correct and y = -3 is to be neglected as it does not satisfy the answer.
Log in to reply
Thats okay.. but why "gradient of tangent?". Its only tangent of "f(x)".
Log in to reply
A tangent is a line that is tangent to the function. A gradient of the tangent is the gradient of this tangent line or the gradient at x=12. The question is accurately phrased.
Log in to reply
@Tong Choo – Tangent at x = 1 2 is also a correct phrasing.. :)
Log in to reply
@Snehal Shekatkar – tangent at x=12 would mean the complete equation of the tangent (y=x/7 + 16/7 ,in this case). The question asks for the gradient, which is 1/7. The question is perfectly phrased. Anyways, what matters is that you understood the problem, so relax!!
@Snehal Shekatkar – No, I don't think tangent would be correct phrasing because it does not specify that I wanted the answer to be the slope of the tangent. Like nikhil said, tangent could be asking for the equation of the tangent, potentially the gradient, or anything else related to the tangent so it would not have worked.
@Tong Choo – I've always heard it as slope rather than gradient
Log in to reply
@Michael Tong – Gradient is synonymous with slope.
Gradient means slope. So the question asks for "slope" of tangent.
Log in to reply
@Nikhil Tiwari – Slope of a function can be defined as its derivative at particular values.
first of all a tangent to the function is f'(x) at x=some 'a' (Which is 12 in our case). Our function can be written as y 2 =x + y. Hence differentiating f(x), we get 2y × d y / d x = 1 + dy/dx. Now, dy/dx = 1/(2y-1) At x=12, f(x)= y 2 = 12 + y which gives y=4 or -3. since the gradient of tangent is positive, we have y=4. Plugging which in f'(x) gives us that dy/dx at x=12 is 1/7. Hence the answer 1+7 = 8
Here is what I did… with some trouble: First, let's get our own definition of the function. g ( x ) = x + g ( x ) So we have a recursive function! Let's find the derivative, so we have a way to find the tangent at 1 2 . (I'll use implicit differentiation.) 2 g ( x ) g ′ ( x ) = 1 + g ′ ( x ) So we have our two functions now. Lets get in the numbers. First, we'll evaluate the original function at 12, and using the quadratic formula, we get: g ( 1 2 ) = 2 1 + 1 + 4 8 = 4 Then back to the derivative… g ′ ( 1 2 ) = 2 g ( 1 2 ) − 1 1 = 8 − 1 1 Finally: a + b = 8
Let N be the RHS, and let y = f ( x ) , Then, we have
y = N
y 2 = N + x
Thus, we have y = y 2 − x and y 2 − y = x . Taking the implicit derivative, we have 2 y d x d y − d x d y = 1 and d x d y = 2 y − 1 1 . We require to find the value of y = N at x = 1 2 .
So, going back to our equation, we have that y 2 − y = 1 2 → ( y − 4 ) ( y + 3 ) = 0 . y has to be a positive value, so y = 4 . Our derivative of the tangent line is then d x d y = 7 1 .
Let's find an explicit solution for f ( x ) . As others have noted, it must satisfy: f ( x ) = x + f ( x ) which, letting y = f ( x ) , we can rearrange as: y 2 − y = x We recognise this as a parabola that has been reflected in the line y = x and has y-intercepts at y = 0 , 1 . The quadratic formula gives us two possible solutions, y = 2 1 ± 2 1 1 + 4 x which are the upper and lower branches of the parabola. Since the tangent to the desired function is positive at x = 1 2 , we are only interested in the upper branch. The derivative of it is: d x d y = 1 + 4 x 1 Evaluating at x = 1 2 we get f ′ ( 1 2 ) = 7 1 and so the answer is 1 + 7 = 8 .
Let us consider y = f(x)
Then y^{2} = x + y
Differentiating with respect to x,
[2 \times y \times \frac{dy}{dx}] = [1 + \frac{dy}{dx}]
Gradient [ \frac{dy}{dx}] = [\frac{1}{ 2 \times y - 1}]
when x =12, y= 4 or (-3)
Since only positive value is asked, y = 4.
so, y =4, [\frac{dy}{dx} ]= [\frac{1{7}] = [\frac{a}{b}]
so, [\boxed{a + b = 8}]
y^2=x+y or, y^2-y-12=0 or, y=-3,4. As y can be expressed as the square root of real number,the value of y can't be negetive. So, y=4.
Now,(dy/dx)=1/(2y-1) for y=4,the value of (dy/dx)=1/7=a/b
So, a+b=8
Let y = f ( x ) .
Find the solution of f ( 1 2 )
As soon as y = x + x + . . .
y = x + y
y 2 − y = x
At x = 1 2 , y = 4 .
Deriving f(x)
d x d y 2 − y = d x d x
d y d y 2 − y y ′ = 1
y ′ = 2 y − 1 1
Concluding
y ′ = b a
y ′ = 7 1
a + b = 8
It forms a quadratic equation in f(x) , since the pattern inside the root is infinite...
f(x)= sqrt(x + f(x)) , which means, after solving using Vieta's formula,
2*f(x) = 1+ sqrt(4x+1)
{after ignoring the other solution having '-' sign with sqrt(4x+1), since f(x) would always be positive}
Differentiating this value of f(x) w.r.t 'x', we get,
f'(x) = 1/sqrt(4x+1)
which gives f'(12) = 1/7 ...
Problem Loading...
Note Loading...
Set Loading...
First step , we shall do a little algebra manipulation. We see that: f ( x ) = x + x + x + . . . f 2 ( x ) = x + x + x + . . . f 2 ( x ) − x = x + x + . . . Note that this is same as the initial equation we're manipulating. Thus we may form an equation: f 2 ( x ) − x = f ( x ) f 2 ( x ) − f ( x ) − x = 0 Factorise this equation and we obtain: ( f ( x ) − 4 ) ( f ( x ) + 3 ) = 0 Therefore, f ( x ) = 4 or f ( x ) = − 3
Second step , now we want to find the equation for the gradient of the function of x. Therefore, we have to find f ′ ( x ) . We may find this using implicit differentiation on the equation: f 2 ( x ) − f ( x ) − x = 0 2 f ( x ) f ′ ( x ) − f ′ ( x ) − 1 = 0 f ′ ( x ) ( 2 f ( x ) − 1 ) = 1 f ′ ( x ) = 2 f ( x ) − 1 1
Third step , plugging the value of f ( x ) = − 3 into f ′ ( x ) = 2 f ( x ) − 1 1 will result in a negative answer, which is contradiction since a and b are positive values. Therefore, we plug in f ( x ) = 4 into f ′ ( x ) = 2 f ( x ) − 1 1 . Hence: f ′ ( x ) = 2 ( 4 ) − 1 1 f ′ ( x ) = 7 1
Our desired answer is 1 + 7 = 8